SISTEM INFORMASI PENJUALAN BERBASIS WEB E-COMMERCE MENGGUNAKAN WATERFALL - Imelda Halawa; Puji Chairu Sabila; Nurul Afni (JURNAL WIDYA, 2025)
The rapid development of information technology presents a significant opportunity for business owners to improve sales efficiency and market reach. UD. Chandra, a trading business engaged in the sale of household necessities such as electronics, sandals, shoes, ready-made clothing, and groceries, still conducts its sales processes conventionally. This results in limited market reach and suboptimal transaction data management. Therefore, a web-based e-commerce sales information system was designed to simplify the transaction process, expand customer reach, and enhance business performance. The development method used in this system is the Waterfall model, which consists of the stages of requirement analysis, system design, implementation, testing, and maintenance. The system is developed using PHP as the programming language and MySQL as the database, with a responsive web-based user interface. The result of this design is an e commerce system that allows customers to place product orders online, and provides features for product management, transactions, and sales reports for administrators. With this system, UD. Chandra is expected to manage its sales processes more effectively and efficiently, and to compete in the digital era by leveraging information technology optimally. Keywords: Information System, E-Commerce, Online Sales, Waterfall, UD. Chandra, Web